Chinese Media Engagement in South Africa: What is its impact on local journalism?. (11th June 2018) - Madrid-Morales, Dani; Wasserman, Herman
Abstract : China's footprint in Africa's media sector over the last decade has reached dimensions that make it impossible to go unnoticed. In South Africa, one of the countries where this imprint is most diversified, Chinese media have been engaged in a varied range of activities, including content production and distribution, infrastructure development, direct investment in local media and training of journalists. Building on previous exploratory studies by the authors, this paper addresses an unresolved question in the study of China's media internationalization: the impact on journalism. Using data from 20 semi-structured in-depth interviews with editors, journalists and policy makers, we investigate how much influence Chinese media exercise on journalism in South Africa. We present responses along three dimensions: consumption of and attitudes towards Chinese media, impact on local journalism and views about South Africa–China relations. Our data offer evidence that, despite having substantially increased their presence, Chinese media are far from having a profound impact on media professionals. While some interviewees report the adoption of some Chinese media in their daily news consumption, scepticism towards China, and by extension its media, dominates. We discuss these findings in the context of Chinese state-owned media's attempts to increase their discursive power globally.